Conductive foam and preparation method thereof
By immersing the open-cell foam in a specially made conductive ink to form a three-dimensional conductive network, the problems of uneven conductivity and complex preparation process of the existing conductive foam are solved, and efficient, uniform and stable preparation of the conductive foam is achieved.
Patent Information
- Application Number
- CN202311151656.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-07
- Publication Date
- 2025-03-07
AI Technical Summary
The existing conductive foam has problems such as uneven conductivity, complex production process, thick overall and large space occupancy.
By immersing the open-cell foam in a specially made conductive ink, and immersing and drying process multiple times, the conductive nanowires are evenly and firmly attached to the surface and pores of the foam under the action of an additive, forming a stable three-dimensional conductive network.
The good conductivity and stability of conductive foam is achieved, the preparation process is simplified, the product thickness and space occupied are reduced, and the conductivity uniformity and stability are improved.
Smart Images

Figure CN119570105A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of conductive material preparation, and in particular to a conductive foam and a preparation method thereof. Background Art
[0002] Conductive foam uses a foamed sponge with excellent elasticity as raw material, and has a large grid breathable grid structure material, and finally composites the conductive material to obtain a product with conductive properties. Conductive foam can be divided into: aluminum foil cloth foam, conductive fiber cloth foam, gold-plated cloth foam, carbon-plated cloth foam, etc., and is widely used in mobile phones, LCD monitors, PDP TVs, LCD TVs, notebook computers, MP3s, communication cabinets, medical instruments and other electronic products as well as military and aerospace fields.
[0003] Existing conductive foams are usually configured by wrapping conductive cloth on the outside of the foam, plating conductive materials (such as metal, carbon, etc.) on the foam, and a structure of foam layer and conductive glue. These conductive foams have problems such as uneven conductive properties, complex manufacturing process, overall thickness, and large space occupation.
[0004] The preparation methods of conductive foam mainly include: (1) one-step synthesis, in which the foam precursor is mixed with the conductive material before the foam is prepared, and then further processed into a shape. Due to the poor compatibility between the conductive material and the foam raw material, the preparation process is complicated, there are many uncontrollable factors, and the product quality varies; (2) vacuum evaporation, in which a conductive layer is coated on the surface of the foam, but the coating is easy to fall off, the product performance decreases rapidly, and the service life is short; (3) dip coating, in which the foam is directly immersed in a conductive material dispersion, but the conductive material and the foam have defects such as poor bonding and uneven dispersion, which further limits the conductive performance of the conductive foam.
[0005] Based on this, there is an urgent need for a conductive foam with a simple preparation process and uniform and stable conductivity. Summary of the invention
[0006] The present invention provides a method for preparing a conductive foam, wherein an open-cell foam is immersed in a special conductive ink, and after multiple immersion and drying treatments, the conductive nanowires in the conductive ink can be evenly and firmly attached to the surface and pores of the open-cell foam under the action of an auxiliary agent, forming a stable three-dimensional conductive network, so that the prepared conductive foam has good conductivity and stability.
[0007] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0008] The first aspect of the present invention provides a method for preparing a conductive foam, comprising dipping an open-cell foam in a conductive ink, taking it out and drying it, and repeating the dipping and drying operations until a conductive foam with a target resistance value is obtained;
[0009] The conductive ink comprises the following components by mass percentage: 0.2%-0.5% conductive nanowires, 0.005%-0.01% surface wetting agent, 0.01%-0.02% dispersant, 0.005%-0.01% crosslinking agent, 0.01%-0.015% coupling agent, and the balance is solvent.
[0010] Furthermore, the preparation method further includes the step of pre-treating the open-cell foam before impregnating the conductive ink, specifically: placing the open-cell foam in ethanol for ultrasonic treatment for 10-30 minutes, and drying to obtain the pre-treated open-cell foam; the ultrasonic frequency of the ultrasonic treatment is 20-25kHz, and the ultrasonic power is 600-900W. The present invention first cleans and pre-treats the open-cell foam before impregnation to remove grease or other impurities on the surface, and at the same time provides a large number of active sites for the foam to improve the adhesion of the silver nanowires on the open-cell foam.
[0011] Furthermore, the infiltration ratio of the open-cell foam to ethanol is preferably 0.5 g: 20-30 mL.
[0012] Furthermore, in the impregnation step, the impregnation time is preferably 3-15 minutes; in the drying step, the drying temperature can be 50-80°C.
[0013] Further, the drying operation is carried out in an infrared radiation heating box;
[0014] The infrared radiation heating box is composed of an insulation box, an infrared radiation heating tube arranged in the insulation box, and a sample tray; the infrared radiation heating tube is arranged at the top and bottom of the insulation box, and the sample tray is arranged in the middle of the insulation box; the infrared radiation heating tube can rotate along the plane in the heating process, and the rotation speed is 1-10 laps / min. During the heat treatment process, the conductive foam is dried in an ordinary oven, which is easy to cause white spots, black spots, shrinkage and deformation of the conductive foam due to uneven heating, hot air impact, etc., thereby reducing the product yield. Based on the above problems found in the experimental process, the present invention designs an infrared thermal radiation heating furnace according to the heating characteristics of wet conductive foam, and uses a rotatable infrared radiation heating tube in a special infrared thermal radiation heating furnace. By controlling the rotation speed of the infrared radiation heating tube, the foam can be effectively heated evenly (if the infrared radiation heating tube does not rotate, the gap between the heating tubes will cause different effective radiation areas for the foam, thereby uneven heating, causing the foam to bend), thereby effectively reducing the shrinkage, deformation, white spots and black spots of the conductive foam during the drying process.
[0015] Furthermore, the wetting ratio of the open-cell foam to the conductive ink is 0.5 g: 10-20 mL.
[0016] Furthermore, the dipping and drying operations are repeated 3-6 times to obtain a conductive foam with a resistance value of 0.01-0.3Ω, where the resistance value is the vertical resistance of the conductive foam of 2mm×6mm (height pressed to 1mm). During the repeated dipping process, the conductive nanowires begin to deposit with the outer surface of the open-cell foam and the side walls of the pores of the open-cell foam as the initial attachment points, and the conductive nanowires gradually overlap each other to form a three-dimensional network, until the outer surface of the open-cell foam and its pores are completely covered by the three-dimensional network of conductive nanowires.
[0017] Furthermore, the material of the open-cell foam is polyethylene foam, polyester foam or rubber foam, but is not limited to the materials listed above; the polyethylene foam includes but is not limited to PE foam, EVA foam, etc., the polyester foam includes but is not limited to polyether foam, polyurethane foam, etc., and the rubber foam includes but is not limited to chloroprene rubber foam, nitrile rubber foam, styrene-butadiene rubber foam, EPDM rubber foam, etc.
[0018] Furthermore, the pore size of the open-cell foam is preferably 200nm-200μm, and the thickness of the open-cell foam is preferably 1mm-5mm. The present invention uses open-cell foam as the substrate of the conductive foam, so that the conductive nanowires can not only form a conductive network on the outer surface of the foam, but also form a three-dimensional conductive network in the pores of the foam, which can improve the conductivity and uniformity of the conductive foam, and also enable the conductive foam to maintain high conductivity under deformation. In addition, under the premise of ensuring the conductive performance of the conductive foam, the thickness and area of the conductive foam are effectively reduced.
[0019] Furthermore, the conductive nanowire is at least one of a silver nanowire, a copper nanowire, a nickel nanowire, a gold nanowire, and a carbon nanowire.
[0020] Furthermore, the diameter of the conductive nanowire is preferably 15nm-60nm, and the length is preferably 10-40μm; the aspect ratio of the conductive nanowire is 100-3000:1. The aspect ratio of the conductive nanowire will affect the dispersion uniformity and stability of the nanosilver wire in the conductive ink and the conductivity of the formed three-dimensional conductive network; if the aspect ratio of the conductive nanowire is too small, although the dispersion uniformity and stability of the conductive nanowire in the conductive ink are good, the three-dimensional conductive network formed has many overlapping points, the conductivity is relatively poor, and the conductive stability is not good under deformation; if the aspect ratio of the conductive nanowire is too large, it is easy to interweave and precipitate in the conductive ink, resulting in uneven distribution of the conductive nanowire on the foam, uneven conductivity of the prepared conductive foam, and other problems.
[0021] Furthermore, the surface wetting agent is selected from one or more of alkyl sulfates, polyoxyethylene alkylphenol ethers, Tween, and dimethyl sulfoxide; the present invention adds a surface wetting agent to the conductive ink to improve the wettability of the surface and pores of the open-cell foam, which helps the conductive ink to evenly infiltrate the foam substrate.
[0022] Furthermore, the dispersant is selected from one or more of polyethylene glycol, fatty alcohol polyoxyethylene ether, hexadecyltrimethylammonium bromide, sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, and ethoxylated alkyl sodium sulfate; the present invention introduces a dispersant into the conductive ink to improve the dispersibility of the conductive nanowires in the conductive ink, avoid local agglomeration, and affect the conductive uniformity of the conductive foam.
[0023] Furthermore, the cross-linking agent is selected from one or more of tetraisocyanate, polypropylene glycol glycidyl ether, ethylene glycol dimethacrylate, and diisopropylbenzene peroxide; the present invention also introduces a cross-linking agent into the conductive ink, and the cross-linking agent remaining in the foam pores reacts with the foam substrate and can fill the foam membrane pores after curing, so that the conductive nanowire network firmly adheres to the membrane pores, thereby improving the stability of the three-dimensional conductive network.
[0024] Furthermore, the coupling agent is a silane coupling agent and / or a titanate coupling agent; the present invention further introduces a coupling agent into the conductive ink to improve the adhesion between the conductive nanowires and the foam substrate, prevent the conductive layer on the surface of the conductive foam and in the pores from falling off under the action of external force, thereby improving the stability of the conductive performance of the conductive foam.
[0025] Furthermore, the solvent is ethanol and / or isopropanol.
[0026] Furthermore, in the preparation process of the conductive ink, the conductive ink is obtained by uniformly mixing the dispersion of the nano silver wires with the other components.
[0027] The second aspect of the present invention provides a conductive foam prepared by the preparation method described in the first aspect.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] 1. The present invention uses an open-cell foam with a porous structure as a substrate, and obtains a conductive foam with good and stable conductivity by multiple immersion and drying treatments in a special conductive ink. Based on the introduction of different additives, the dispersion and agglomeration problems of conductive nanowires can be effectively improved. The conductive nanowires can be evenly and stably dispersed in the conductive ink, thereby improving the distribution uniformity of the conductive nanowires on the foam substrate, which is beneficial to the improvement of the conductive uniformity of the conductive foam. At the same time, under the comprehensive effect of the above additives, the binding force between the conductive nanowires and the foam substrate is effectively improved, so that the conductive stability of the conductive foam is significantly improved; in addition, based on the pores of the open-cell foam, through the above immersion treatment, the conductive nanowires can construct a three-dimensional conductive network on the foam surface and inside the holes, which is beneficial to the improvement of the conductivity and stability of the conductive foam. The present invention improves the conductive foam substrate structure and the conductive ink formula. Under the synergistic effect of the two, a conductive foam with high conductivity, good conductive uniformity and good stability can be obtained by a simple immersion method. The method is simple and easy to operate and suitable for industrial production.
[0030] 2. The present invention designs an infrared thermal radiation heating furnace according to the heating characteristics of wet conductive foam. The rotatable infrared radiation heating tube of the infrared thermal radiation heating furnace and its rotation can effectively ensure that the foam is heated evenly, thereby effectively reducing the shrinkage, deformation, white spots and black spots of the conductive foam during the drying process, which is beneficial to improving the product yield. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a picture of open-cell foam;
[0032] Figure 2 This is a picture of conductive foam;
[0033] Figure 3 The schematic diagram of the structure of the infrared heat radiation heating furnace, where ① is the insulation box, ② is the infrared radiation heating tube, and ③ is the sample tray;
[0034] Figure 4 It is a schematic diagram of the structure before and after the conductive foam hole is filled;
[0035] Figure 5 This is a SEM image of the conductive foam prepared in Example 1;
[0036] Figure 6 This is the SEM image of the conductive foam prepared in Comparative Example 3. DETAILED DESCRIPTION
[0037] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are for the purpose of describing specific embodiments only and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items. The term "includes" or "comprising" described in the present invention means that it may include or contain other components in addition to the components described. The term "includes" or "comprising" described in the present invention may also be replaced by the closed form "for" or "consisting of..."
[0038] The present invention is further described below in conjunction with specific embodiments and drawings so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0039] Example 1
[0040] This embodiment provides a preparation method of a conductive foam, which is as follows:
[0041] (1) 0.5 g of foam was immersed in 20 mL of ethanol and ultrasonically treated for 20 min, wherein the ultrasonic frequency was 20 kHz and the ultrasonic power was 750 W. After being taken out, the foam was dried to obtain the pretreated foam.
[0042] (2) The ethanol dispersion of nanosilver wires is uniformly mixed with polyoxyethylene alkylphenol ether, sodium ethoxylated alkyl sulfate, polypropylene glycol glycidyl ether and silane coupling agent to obtain a conductive ink, wherein the weight proportions of the components in the conductive ink are as follows: 0.2% nanosilver wires, 0.008% polyoxyethylene alkylphenol ether, 0.015% sodium ethoxylated alkyl sulfate, 0.005% polypropylene glycol glycidyl ether, 0.01% silane coupling agent, and the balance is ethanol.
[0043] Immerse the foam pretreated in step (1) in the conductive ink prepared in step (2) for 10 minutes, take it out with tweezers, put it in a watch glass, and place it as follows: Figure 3 In the sample tray of the infrared thermal radiation heating furnace shown, the rotation speed of the infrared radiation heating tube is set to 5 revolutions / min, and the sample is dried in the 50°C infrared thermal radiation heating furnace for 90 minutes. After the solvent evaporates completely, the above-mentioned dipping and drying process is repeated, and the conductive foam is obtained by repeating the process 3 times.
[0044] Example 2
[0045] This embodiment provides a preparation method of a conductive foam, which is as follows:
[0046] (1) 0.5 g of foam was immersed in 20 mL of ethanol and ultrasonically treated for 20 min, wherein the ultrasonic frequency was 20 kHz and the ultrasonic power was 750 W. After being taken out, the foam was dried to obtain the pretreated foam.
[0047] (2) The ethanol dispersion of nanosilver wires was uniformly mixed with dimethyl sulfoxide, sodium dodecylbenzene sulfonate, polypropylene glycol glycidyl ether and silane coupling agent to obtain a conductive ink. The weight proportions of the components in the conductive ink were as follows: 0.3% nanosilver wires, 0.01% dimethyl sulfoxide, 0.015% sodium dodecylbenzene sulfonate, 0.005% polypropylene glycol glycidyl ether, 0.01% silane coupling agent, and the balance was ethanol.
[0048] (3) Immerse the foam pretreated in step (1) in the conductive ink prepared in step (2) for complete immersion for 10 minutes, take it out with tweezers, put it in a watch glass, and dry it in a 50°C infrared thermal radiation heating furnace (speed of 5 revolutions / min) for 90 minutes. After the solvent evaporates completely, repeat the above immersion and drying process, and repeat it three times to obtain the conductive foam.
[0049] Example 3
[0050] This embodiment provides a preparation method of a conductive foam, which is as follows:
[0051] (1) 0.5 g of foam was immersed in 20 mL of ethanol and ultrasonically treated for 20 min, wherein the ultrasonic frequency was 20 kHz and the ultrasonic power was 750 W. After being taken out, the foam was dried to obtain the pretreated foam.
[0052] (2) The ethanol dispersion of the nanosilver wires was uniformly mixed with Tween, sodium ethoxylated alkyl sulfate, polypropylene glycol glycidyl ether and silane coupling agent to obtain a conductive ink, wherein the weight proportions of the components in the conductive ink were as follows: 0.4% nanosilver wires, 0.01% Tween, 0.015% sodium ethoxylated alkyl sulfate, 0.005% polypropylene glycol glycidyl ether, 0.01% silane coupling agent, and the remainder was ethanol.
[0053] (3) Immerse the foam pretreated in step (1) in the conductive ink prepared in step (2) for complete immersion for 10 minutes, take it out with tweezers, put it in a watch glass, and dry it in a 50°C infrared thermal radiation heating furnace (speed of 5 revolutions / min) for 90 minutes. After the solvent evaporates completely, repeat the above immersion and drying process, and repeat it three times to obtain the conductive foam.
[0054] Example 4
[0055] This embodiment provides a preparation method of a conductive foam, which is as follows:
[0056] (1) 0.5 g of foam was immersed in 20 mL of ethanol and ultrasonically treated for 20 min, wherein the ultrasonic frequency was 20 kHz and the ultrasonic power was 750 W. After being taken out, the foam was dried to obtain the pretreated foam.
[0057] (2) The isopropyl alcohol dispersion of the nanosilver wire is evenly mixed with polyoxyethylene alkylphenol ether, sodium ethoxylated alkyl sulfate, polypropylene glycol glycidyl ether and silane coupling agent to obtain a conductive ink, wherein the weight proportions of the components in the conductive ink are as follows: 0.5% nanosilver wire, 0.008% polyoxyethylene alkylphenol ether, 0.015% sodium ethoxylated alkyl sulfate, 0.009% polypropylene glycol glycidyl ether, 0.012% silane coupling agent, and the balance is isopropyl alcohol.
[0058] (3) Immerse the foam pretreated in step (1) in the conductive ink prepared in step (2) for complete immersion for 10 minutes, take it out with tweezers, put it in a watch glass, and dry it in a 50°C infrared thermal radiation heating furnace (speed of 5 revolutions / min) for 90 minutes. After the solvent evaporates completely, repeat the above immersion and drying process, and repeat it three times to obtain the conductive foam.
[0059] Comparative Example 1
[0060] This comparative example provides a preparation method for a conductive foam, which is different from Example 3 only in that the components of the conductive ink are as follows:
[0061] The weight proportions of the components in the conductive ink prepared in this comparative example are as follows: 0.4% nano silver wires and the balance ethanol.
[0062] Comparative Example 2
[0063] This comparative example provides a preparation method for a conductive foam, which is different from Example 3 only in that the components of the conductive ink are as follows:
[0064] The weight proportions of the components in the conductive ink prepared in this comparative example are as follows: 0.4% nanosilver wire, 0.008% dimethyl sulfoxide, and the balance is ethanol.
[0065] Comparative Example 3
[0066] This comparative example provides a preparation method for a conductive foam, which is different from Example 3 only in that the components of the conductive ink are as follows:
[0067] The weight proportions of the components in the conductive ink prepared in this comparative example are as follows: 0.4% nanosilver wire, 0.01% dimethyl sulfoxide, 0.015% ethoxylated sodium alkyl sulfate, and the balance is ethanol.
[0068] Comparative Example 4
[0069] This comparative example provides a preparation method for a conductive foam, which is different from Example 3 only in that the components of the conductive ink are as follows:
[0070] The weight proportions of the components in the conductive ink prepared in this comparative example are as follows: 0.4% nanosilver wire, 0.008% dimethyl sulfoxide, 0.015% ethoxylated sodium alkyl sulfate, 0.009% polypropylene glycol glycidyl ether, and the balance is ethanol.
[0071] Comparative Example 5
[0072] This comparative example provides a preparation method for a conductive foam, which differs from Example 3 only in the rotation speed of the heat treatment furnace, which is specifically as follows: drying in a 50° C. infrared heat radiation heating furnace (rotation speed is 0 rpm) for 90 min.
[0073] The formula of the conductive ink and the heat treatment process parameters in the above embodiments and comparative examples are shown in Table 1 below:
[0074] Table 1
[0075]
[0076]
[0077] Performance Testing
[0078] Taking Example 1 and Comparative Examples 1 to 5 as examples, the vertical resistance of different conductive foams was tested, and the specific operation was as follows:
[0079] Select 10 different positions of 0.6×11cm conductive foam (the selected positions of different samples are the same), cut it into 0.6×0.2cm samples, and use a high-precision foam compression resistance tester to test the resistance. The compression fixture is divided into two parts, the upper and lower parts. Put the cut foam in the middle and press it to a thickness of 1mm. Then use alligator clips to clamp the upper and lower ends of the stage, press the switch, start the test, and record the digital resistance value. If no value is displayed, it is recorded as a failure point. Among them, the more failure points there are, the more uneven the conductive performance of the conductive foam is.
[0080] The test results are shown in Table 2 below:
[0081] Table 2
[0082] Location Example 1 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 1 70mΩ Failure Point Failure Point Failure Point Failure Point 2 69mΩ Failure Point 70mΩ Failure Point 75mΩ 3 69mΩ 56mΩ 67mΩ 67mΩ 73mΩ 4 68mΩ Failure Point Failure Point Failure Point 68mΩ 5 69mΩ Failure Point 91mΩ Failure Point 69mΩ 6 69mΩ Failure Point 99mΩ Failure Point 84mΩ 7 68mΩ Failure Point Failure Point Failure Point 82mΩ 8 69mΩ Failure Point 78mΩ Failure Point 90mΩ 9 69mΩ Failure Point Failure Point Failure Point 85mΩ 10 69mΩ Failure Point Failure Point Failure Point 84mΩ
[0083] It can be seen from Table 2 above that under the combined effect of various additives, the conductive foam prepared in Example 1 has the best uniformity, and no failure point is found at the sampling point, while Comparative Examples 1-4 all have failure points; Figure 5The SEM image of the conductive foam prepared in Example 1 shows that the silver nanowire network formed on the surface is dense, uniform and tightly combined with the foam substrate, while the SEM image of the conductive foam prepared in Comparative Example 3 is as follows: Figure 6 As shown, the distribution of nano silver wires on the foam surface is small and uneven, and the formed nano silver wire network is not completely adhered to the foam surface and is easy to fall off. The resistance values of the non-failed parts in Comparative Examples 2 and 4 are quite different, and the uniformity is poor.
[0084] According to the above vertical resistance test method, 10 different positions were selected to test the average resistance of the conductive foam prepared in Examples 1-4. The test results are shown in Table 3 below:
[0085] Table 3
[0086] Sample Average resistance Example 1 69mΩ Example 2 53mΩ Example 3 35mΩ Example 4 51mΩ
[0087] It can be seen from Table 3 that with the increase of the content of nano-silver wires in the conductive ink, the average resistance of the conductive foam first decreases and then increases. It is speculated that this is because when the content of nano-silver wires in the conductive ink increases to a certain value, the content of nano-silver wires continues to increase, and the nano-silver wires in the conductive ink are prone to interweaving and thus settling, which will in turn reduce the content of suspended nano-silver wires in the conductive ink.
[0088] In addition, the sample after the vertical resistance test is placed under a 200X microscope to observe the white spots on its surface. If the number of white spots on the surface of the sample is greater than 3, it is considered unqualified.
[0089] The number of white spots on the surface of the conductive foam is shown in Table 4:
[0090] Table 4
[0091] Treatment Number of white spots Eligibility Comparative Example 1 >20 no Comparative Example 2 >19 no Comparative Example 3 <3 yes Comparative Example 4 <3 yes Example 1 <3 yes
[0092] It can be seen from Table 4 that the number of white spots on the surface of the conductive foam prepared in Example 1 and Comparative Examples 3 and 4 is relatively small. It can be seen from Comparative Examples 3 and 4 and Comparative Examples 1 and 2 that the addition of dispersant and cross-linking agent can effectively improve the conductive uniformity of the conductive foam.
[0093] In addition, Example 3 and Comparative Example 5 both use an infrared radiation heating furnace to dry the samples, the only difference being the rotation speed of the infrared radiation heating tube. An optical microscope is used to observe the morphology of the conductive foam after drying at different rotation speeds. The results are shown in Table 5 below:
[0094] Table 5
[0095]
[0096] As shown in Table 5, the conductive foam obtained by heating the infrared radiation tube without rotating it in Comparative Example 5 shrinks and deforms. However, by adjusting the rotation speed of the infrared radiation tube, the heating uniformity of the sample can be improved, and the correspondingly prepared sample will not shrink or deform, which is beneficial to improving the conductivity uniformity of the sample and the product yield.
[0097] The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Equivalent substitutions or changes made by those skilled in the art based on the present invention are within the protection scope of the present invention. The protection scope of the present invention shall be subject to the claims.
Claims
1. A method for preparing a conductive foam, characterized in that: Dipping the open-cell foam in the conductive ink, taking it out and drying it, repeating the dipping and drying operations until a conductive foam with a target resistance value is obtained; The conductive ink comprises the following components by mass percentage: 0.2%-0.5% conductive nanowires, 0.005%-0.01% surface wetting agent, 0.01%-0.02% dispersant, 0.005%-0.01% crosslinking agent, 0.01%-0.015% coupling agent, and the balance is solvent.
2. The preparation method according to claim 1, characterized in that: The preparation method also includes the step of pretreating the open-cell foam before impregnating the conductive ink, specifically: placing the open-cell foam in ethanol for ultrasonic treatment for 10-30 minutes, and drying to obtain the pretreated open-cell foam; the ultrasonic frequency of the ultrasonic treatment is 20-25kHz, and the ultrasonic power is 600-900W.
3. The preparation method according to claim 1, characterized in that: The infiltration ratio of the open-pore foam to the conductive ink is 0.5 g: 10-20 mL.
4. The preparation method according to claim 1, characterized in that: In the impregnation step, the impregnation time is 3-15 minutes; in the drying step, the drying temperature is 50-80°C.
5. The preparation method according to claim 1, characterized in that: The drying operation is carried out in an infrared radiation heating box; The infrared radiation heating box consists of an insulation box, an infrared radiation heating tube arranged in the insulation box, and a sample tray; the infrared radiation heating tube is arranged at the top and bottom of the insulation box, and the sample tray is arranged in the middle position of the insulation box; the infrared radiation heating tube can rotate along the plane in which it is located during the heating process, and the rotation speed is 1-10 turns / min.
6. The preparation method according to claim 1, characterized in that: Repeat the dipping and drying operations 3-6 times to obtain a conductive foam with a resistance value of 0.01Ω-0.3Ω.
7. The preparation method according to claim 1, characterized in that: The material of the open-cell foam is polyethylene foam, polyester foam or rubber foam; The pore size of the open-cell foam is 200nm-200μm, and the thickness of the open-cell foam is 1mm-5mm.
8. The preparation method according to claim 1, characterized in that: The conductive nanowire is at least one of a silver nanowire, a copper nanowire, a nickel nanowire, a gold nanowire, and a carbon nanowire; The diameter of the conductive nanowire is 15nm-60nm, and the length is 10-40μm; the aspect ratio of the conductive nanowire is 100-3000:
1.
9. The preparation method according to claim 1, characterized in that: The surface wetting agent is selected from one or more of alkyl sulfates, polyoxyethylene alkylphenol ethers, Tween, and dimethyl sulfoxide; The dispersant is selected from one or more of polyethylene glycol, fatty alcohol polyoxyethylene ether, hexadecyltrimethylammonium bromide, sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, and ethoxylated alkyl sodium sulfate; The cross-linking agent is selected from one or more of tetraisocyanate, polypropylene glycol glycidyl ether, ethylene glycol dimethacrylate, and dicumyl peroxide; The coupling agent is a silane coupling agent and / or a titanate coupling agent; The solvent is ethanol and / or isopropanol.
10. A conductive foam prepared by the preparation method according to any one of claims 1 to 9.